2007
DOI: 10.1088/0953-8984/19/38/386223
|View full text |Cite
|
Sign up to set email alerts
|

The nature of electron states in AlN and α-Al2O3

Abstract: The nature of electron states in AlN and alpha-Al2O3Fang, C. M.; de Groot, R. A. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. Abstract Both α-alumina and aluminium nitride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The bulk of the sapphire crystal is made up of α-Al 2 O 3 , which has corundum structure, and the coordination number of aluminum atoms in this structure is 6. Experimental and theoretical studies of electronic band structure of crystalline and amorphous alumina are available in the literature [18][19][20][21]33,34]. The absorption features at A and B can be explained as the excitation of 2p electrons of six coordinated Al 3 ions to the top of the valence band and the bottom of conduction band of α-Al 2 O 3 , respectively.…”
Section: Fine Structure In Absorption Of Sapphire Crystalmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the sapphire crystal is made up of α-Al 2 O 3 , which has corundum structure, and the coordination number of aluminum atoms in this structure is 6. Experimental and theoretical studies of electronic band structure of crystalline and amorphous alumina are available in the literature [18][19][20][21]33,34]. The absorption features at A and B can be explained as the excitation of 2p electrons of six coordinated Al 3 ions to the top of the valence band and the bottom of conduction band of α-Al 2 O 3 , respectively.…”
Section: Fine Structure In Absorption Of Sapphire Crystalmentioning
confidence: 99%
“…Absorption in even higher energy range has been determined and the spin-orbit doublet of the Al 3 L II;III is revealed at 78.67 and 79.12 eV for the case of α-Al 2 O 3 [13]. For the sake of completion it can be mentioned here that several theoretical investigations have been carried out on the band structure of both amorphous and crystalline Al 2 O 3 , which can help in predicting its optical properties [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The structure and properties of a crystal is determined by the interaction of the valence electrons of the elements in the crystal. Electronic structure theory provided that both the valence bands and lower parts of the conduction bands of MgO and α-Al 2 O 3 are dominated by the O 2p and O 3s states, respectively, which suggests that the structures of these ionic oxides are determined mainly by the O sub-lattices [19,20]. Therefore, it is rational to consider the dense O-layer in both oxides as the termination layer.…”
Section: Introductionmentioning
confidence: 99%
“…Hird14 reported that the intensity of TL emission during diamond polishing in ‘hard’ direction is greater than ‘soft’ direction. The crystallographic orientation of Al 2 O 3 influences the atomic and electronic structures of alumina surfaces15. Brewer et al 16.…”
mentioning
confidence: 99%